Análisis de la representación de la mujer en la publicidad de la revista Cosmopolitan. - Mejía Sampedro, Jhael Eliana (2016)
This article has as a principal theme the analysis of the representation of the women in the advertisements of the magazine Cosmopolitan between May, June and July of 2014. The purpose is to know the form that the women is represent, the stereotypes that are managed by the public advertisements at the moment, and how the public is identify with the advertisement according with the marks and products. Considering that the magazine is for woman where they are represent with a lot of make up inside the ambits of the movie, television and fashion that transmit the society that the physical is important in some spaces. The analysis that is realized try to identify to what people is this magazine, in according with the marks, products and models that appear to know under what stereotypes is represent the women in the present, if they have schemes of inclusion or exclusion.